2019
DOI: 10.1111/codi.14557
|View full text |Cite
|
Sign up to set email alerts
|

Colon capsule endoscopy for colonic surveillance

Abstract: Aim Resources used in surveillance colonoscopies are taking up an increasing proportion of colonoscopy capacity. Colon capsule endoscopy (CCE) is a promising technique for noninvasive investigation of the colon. We aimed to investigate CCE as a possible filter in colonic surveillance with the primary outcome of reducing the number of colonoscopies.Method Patients scheduled for follow-up colonoscopy were subjected to a primary CCE and only supplemental conventional endoscopy if significant pathology was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…In all concurrent validity studies comparing CCE to colonoscopy, it has detected all colorectal cancers (100% sensitivity/specificity). A recent Danish surveillance study has used CCE as a filter to colonoscopy and demonstrated a reduction in the number of colonoscopies required [16]. Given CCE’s high sensitivity for detection of pathology, we suggest its use as a triaging tool, particularly when pressure on endoscopy units is likely to be high.…”
Section: Figurementioning
confidence: 99%
“…In all concurrent validity studies comparing CCE to colonoscopy, it has detected all colorectal cancers (100% sensitivity/specificity). A recent Danish surveillance study has used CCE as a filter to colonoscopy and demonstrated a reduction in the number of colonoscopies required [16]. Given CCE’s high sensitivity for detection of pathology, we suggest its use as a triaging tool, particularly when pressure on endoscopy units is likely to be high.…”
Section: Figurementioning
confidence: 99%
“…The accuracy of CCE in post-polypectomy surveillance has not been carefully investigated. Only one study investigated CCE as a possible filter test in colonic surveillance in patients scheduled for follow-up colonoscopy [100]. In this study, 102 of 180 patients (57 %) who underwent CCE also underwent a supplemental colonoscopy, because either significant pathology was detected on CCE or CCE examination was incomplete.…”
Section: Cce In Post-polypectomy Surveillancementioning
confidence: 99%
“…Consequently, post-CCE colonoscopy referral of these patients may be expected to lead to a substantial reduction of the prevalence of advanced neoplasia in patients initially evaluated with CCE. Using a cutoff of significant findings defined as no more than 2 polyps of 10 mm, 43 % of patients have avoided colonoscopy; however, high risk findings were detected in only 10.7 % of patients who underwent colonoscopy [100]. This approach entails that small polyps will be left untreated until the subsequent follow-up.…”
Section: Follow-up Of Cce Findingsmentioning
confidence: 99%
“…More precisely, this study proposes a model that can identify the two flexures, ascending-, transverse-, and descending-colon parts of the large intestine. In many cases, polyp identified by CCE is not found in the succeeding colonoscopy [ 13 , 14 ], and, thus, such information is of clinical importance to the physicians, as it narrows down the location of the disease, reducing the time and ambiguity of following therapeutic endoscopies and increased chance of successful identification of polyps.…”
Section: Introductionmentioning
confidence: 99%